Sosialisasi Manfaat Pentingnya Mengonsumsi Ikan Segar di SMPN 5 Sambas - Asrin, Asrin; Ervandi, Ervandi; Rosada, Fadia; Hafizin, Hafizin; Agam, Beryaldi (Hippocampus: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community service activity aims to increase students' understanding and awareness of the importance of consuming fresh fish as a source of nutritious and safe food for body health. This activity was carried out at SMPN 5 Sambas with a target of 30 grade 8 students. The methods used include lectures, interactive discussions, counseling through animated video media, and question and answer sessions that encourage active student participation. The material presented included the definition of fish, the benefits of fish consumption, and how to distinguish fresh and unfresh fish. Giving gifts to students who are able to answer questions correctly is a form of appreciation and motivation. This activity was closed with a photo session with students and principals as documentation. The results of the activity show that an interactive educational approach is able to increase students' knowledge regarding the benefits of consuming fresh fish. It is hoped that this activity can form better fish consumption habits among students.